Intimate Japan : Ethnographies of Closeness and Conflict - Cook, Emma E.; Alexy, Allison (Book collections on Project MUSE., 2019)
In contemporary Japan, as the Japanese population ages, the low birth rate shrinks the population, and decades of recession radically restructure labor markets' intimate relationships, norms, and ideals are concurrently shifting. This volume explores a broad range of intimate practices in Japan in the first decades of the 2000s to trace how social change is manifests through deeply personal choices. From young people making decisions about birth control to spouses struggling to connect with each other, parents worrying about stigma faced by their adopted children, and queer people creating new terms to express their identifications, Japanese intimacies are commanding a surprising amount of attention, both within and beyond Japan. With ethnographic analysis focused on how intimacy is imagined, enacted, and discussed, the volume offers rich and complex portraits of how people balance personal desires with feasible possibilities and shifting social norms.